Revisiting the Toolbox of Discourse Studies New Trajectories in Methodology, Open Data, and Visualization - Rheindorf, Markus; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book revisits discourse analytic practice, analyzing the idea that the field has access to, provides, or even constitutes a 'toolbox' of methods. The precise characteristics of this toolbox have remained largely un-theorized, and the author discusses the different sets of tools and their combinations, particularly those that cut across traditional divides, such as those between disciplines or between quantitative and qualitative methods. The author emphasizes the potential value of integrating methods in terms of triangulation and its specific benefits, arguing that current trends in Open Science require Discourse Studies to re-examine its methodological scope and choices, and move beyond token acknowledgements of 'eclecticism'. In-depth case studies supplement the methodological discussion and demonstrate the challenges and benefits of triangulation. This book will be a valuable resource for students and scholars in Discourse Studies, particularly those with an interest in combining methods and working across disciplines. Markus Rheindorf is Senior Postdoctoral Researcher in the Department for Linguistics at the University of Vienna, Austria.
Chapter 1: Introduction -- Chapter 2: Working with Corpora Small and Large: Qualitative and Quantitative Methods -- Chapter 3: Working with Different Types of Data: Methodological Plurality within and beyond the Linguistic -- Chapter 4: Combining Analyses at Different Levels of Discourse -- Chapter 5: From Synchronic to Diachronic Perspectives: Mapping Change across Time -- Chapter 6: Visualization, Interactive Visualization, and Open Science -- Chapter 7: Case Study 1: Retold Narratives of Holocaust Survivors and Their Children -- Chapter 8: Case Study 2: Normalization of Populist Terms in Political Discourse and Beyond: The 'Unwillingness to Integrate' -- Chapter 9: Case Study 3: Media Representations of Refugees, Asylum Seekers, Immigrants, and Migrants -- Chapter 10: Case Study 4: A Diachronic View of Register and Argumentation in Early Film Theory -- Chapter 11: Concluding Remarks.
Keywords: Linguistics -- Methodology; Computational linguistics; Digital humanities; Motion pictures; Research Methods in Language and Linguistics; Computational Linguistics; Digital Humanities; Film Theory